Fabrication of Ag-Doped ZnO Photocatalysts Derived From MIL-125(Zn) With Enhanced Photocatalytic Activity - Yang, Xiaobing; Yang, Xiangrui; Wu, Shichao (Frontiers in Energy Research, 2022)
Metal-organic frameworks (MOFs) have been widely used in various fields, including gas storage, separation, sensors, and catalysis, owing to their excellent performance. In this study, a zinc-based MOF (MIL-125(Zn))was successfully synthesized using the solvothermal method, and Ag-doped ZnO (Ag/ZnO) was prepared by pyrolyzing Ag/MIL-125(Zn). The fabricated Ag/ZnO was used as a photocatalyst for rhodamine (RhB) degradation. Results show that the MIL-125(Zn) derived from Ag/ZnO exhibits superior photocatalytic activity. It can degrade 99.4% of RhB under 20-min ultraviolet (UV) light irradiation, higher than those achieved using ZnO (73.2%) and MIL-125(ZnO) (19.6%). Furthermore, Ag/ZnO shows excellent stability. After four photocatalytic degradation cycles, the photocatalytic activity of Ag/ZnO reduces by only 3.6%. The excellent photocatalytic performance of Ag/ZnO may be attributed to the synergistic effect of Ag nanoparticles and ZnO. The possible photocatalytic mechanism of RhB degradation on Ag/ZnO photocatalyst under UV light irradiation was proposed.